How comfortable are Malaysian users in utilizing webpages of small businesses? - Abdullah, Moha Asri; Alom, Fardous; Juhdi, Nurita; Mohamad, Noorihsan; Yusuf, Muhammad-Bashir; Azam, S. M. Ferdous (Athens Institute for Education & Research, 2015)
The main objective of the current study is to explore the challenges the Malaysian consumers face in terms of e-commerce experiences with small businesses in general. In addition, the study looks into the potential impacts of demographic profiles of respondents on the e-commerce experiences in general and bad experiences in particular. The results suggest that e-commerce users face highest challenges with after purchase services followed by overall quality, usage experience, value, and installation. Regarding bad experiences, slow internet appears on the top of the list followed by slow delivery of the products, unfriendly website, poor quality products, complicated payment system, and unsecured operations. Also, this study reveals that security issue is no longer serious issue for Malaysian customers. The demographic characteristics have significant impacts on the level of satisfaction perceived in the e-commerce transaction while regarding bad experiences the demographic profiles have little or no impacts.